EFFECT OF PROTOZOAN ON THE EFFICIENCY OF MICROBIAL PROTEIN SYNTHESIS: A REVIEW - POSSAMAI, A. P.S; LALA, B.; PEREIRA, V. V.; MORA, N. H.A.P.; SENEGALHE, F. B.D. (Revista Brasileira de Engenharia de Biossistemas, 2011)
The microbiology of the rumen is a complex and wide due to the large number of organisms present in it, modifications in diet promote changes in the environment and consequently in the microflora present there. Determination of the concentration and composition of the fauna in ruminants on various types of food, are important for the elucidation of the presence of protozoa in the rumen and its relations with the host. In this review are analyzed the effects of defaunation of the rumen, and possible responses to productive ruminants